ANALISIS STRATEGI PENGENDALIAN BIAYA OPERASIONAL DI GRAND MOZZA HOTEL TIMIKA (STUDI KASUS STANDARISASI BIAYA OPERASIONAL - Helviyan Mahendra; Muh. Sabir (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2020)
This study aims to determine the existence of deviations from the budget towards the realization of operational costs at the Grand Mozza Timika Hotel. The method used in this research is descriptive method, which aims to collect budget and realization data in a period that has been completed. Data collection tools used in this research were interview and documentation methods, with data analysis instruments namely analysis of variance (difference) budget against realization. The results of this study indicate that the operational cost budget at each department of the Grand Mozza Timika Hotel produces a favorable and unfavorable difference. However, the overall total operational cost of Hotel Grand Mozza Timika in a period of 1 year shows a favorable difference. It can be proven that the budgeted cost is Rp10,180,676,012 and the realized cost is Rp. 8,086,809,702 has a cost variance of Rp. 2,093,866,311 with a value of 21%, which is very efficient. This means that the cost control strategy for the preparation of the Grand Mozza Timika Hotel operational cost budget has been running but has not functioned properly